Addressing the Global Deforestation Problem through the EU Deforestation Regulation and Producing Countries' Adaptation Processes - Glorya Evanglica Gala; Suryo Sakti Hadiwijoyo; Petsy Jessy Ismoyo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
The European Union's awareness of the importance of forest protection and conservation has led to the European Union Deforestation Regulation (EUDR), which strictly regulates trade in commodities and products that contribute significantly to deforestation and forest degradation. In response to the establishment of this regulation, objections were raised by producer countries of related commodities and products, including Brazil, Ghana, and Indonesia. Therefore, this study will examine the responses and adaptation processes of Brazil, Ghana, and Indonesia to the implementation of the EUDR and analyze the handling of global deforestation through the EUDR from the perspective of Robyn Eckersley's green theory. This study employs a descriptive qualitative approach, utilizing data collection techniques through a literature review of various relevant studies. PEST analysis is used to review the political, economic, social, and technological impacts of the EUDR on producing countries. The results show that Brazil, Ghana, and Indonesia have adopted national approaches in preparing for EUDR implementation. The establishment of the EUDR is a commendable innovation in minimizing environmental damage through binding regulations; however, it is insufficient in reducing global deforestation rates, as these regulations only control access to the European Union market. Examining the EUDR from the perspective of green theory reveals that these regulations remain predominantly human-centric, and their formation process is not ideal based on the fundamental aspects outlined in green theory. Reviewing the impact of the EUDR on political, economic, social, and technological aspects in producer countries underscores the need for EU support for these countries, given the various challenges they face in the adaptation process, even though this regulation encourages more sustainable agricultural practices.